Становлення нових інтелектуальних еліт: інтелігенція, культуральність чи культуртрегерство - Фрадкіна, Наталя Володимирівна (НТУ "ХПІ", 2015)
У статті розмірковується про роль інтелігента у постмодерній культурі. Аналізуються різнобічні підходи щодо діяльності інтелектуалів у сучасному техногенному суспільстві, яке трансформує їх головну соціальну функцію, в результаті чого презентуються їх нові замінники. Підкреслюється негативний вплив масової культури, що значно змінює установки і цінності інтелектуала у старому значенні цього слова. Наголошується на етичній складовій визначення інтелігенції, яка в сучасній культурі набуває нового сенсу і змісту.

The article talks about the role of the intellectual in the postmodern culture. The author considers the issue of new challenges for intellectual elite nowadays. Comprehensive approaches that analyze the activities of intellectuals in modern technological society that transforms their main social function, with the result that presented their new replacements. It emphasized the negative impact of mass culture, which greatly changes the attitudes and values of the intellectual in the old sense of the word. There ethical component of the definition of the intelligentsia, which in modern culture takes on new meaning and content. The development of new technologies and the information revolution are not removed, and increase as the ethical responsibility of the intelligentsia and its professional competence, which takes an interdisciplinary universal.
The formation of new intellectual elites, intelligentsia, kulturalnost or kulturtreherstvo
Keywords: постмодерна культура; нанотехнології; інформаційне суспільство; відповідальність; ціннісні орієнтири; postmodern culture; Nanotechnology; nformational society; responsibility